Impact of Increased Gadget Use on Kindergarten Children’s Behavior During the COVID-19 Pandemic - Sarah Kirana Ridwan; Lucia Pudyastuti Retnaningtyas; Ervin Dyah Ayu Masita Dewi (International Journal of Biomedical Science and Travel Medicine, 2026)
Background: The COVID-19 pandemic caused major disruptions in educational systems worldwide, including early childhood education. Kindergarten learning shifted from face-to-face instruction to online learning, increasing children’s exposure to digital devices. Increased screen exposure may influence children’s behavioural development, particularly emotional regulation, discipline, and social interaction. Objective: This study aimed to explore behavioural changes associated with increased gadget use among kindergarten children during the COVID-19 pandemic. Methods: This qualitative study employed an interpretative descriptive approach. Data were collected through semi-structured interviews with six parents of kindergarten students and one teacher as a triangulation source at Dharma Wanita Persatuan Pepelegi Kindergarten, Waru, Sidoarjo, Indonesia. Participants were selected using purposive sampling. Interview recordings were transcribed verbatim and analysed using inductive thematic analysis. Results: Children’s gadget use increased during the pandemic due to online learning demands and environmental factors such as limited supervision and restricted outdoor activities. Although social interaction with peers remained relatively maintained in some contexts, increased gadget exposure was associated with emotional responses including irritability and frustration when use was restricted, as well as reduced behavioural discipline such as delaying tasks and decreased responsiveness to parental instructions. Conclusion: Increased gadget use during the pandemic was associated with behavioural changes among kindergarten children, particularly in emotional responses and discipline. Environmental conditions and parental supervision played important roles in moderating these effects. Structured guidance and balanced digital media use are therefore essential to support healthy behavioural development in early childhood.